2023
DOI: 10.3390/brainsci13050710
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of SSVEP-BCI Virtual Reality Stereo Stimulation Parameters Based on Knowledge Graph

Abstract: The steady-state visually evoked potential (SSVEP) is an important type of BCI that has various potential applications, including in virtual environments using virtual reality (VR). However, compared to VR research, the majority of visual stimuli used in the SSVEP-BCI are plane stimulation targets (PSTs), with only a few studies using stereo stimulation targets (SSTs). To explore the parameter optimization of the SSVEP-BCI virtual SSTs, this paper presents a parameter knowledge graph. First, an online VR stere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Green and colors with smaller wavelength such as red performed the best in terms of their SSVEP response, SNR and accuracy [14,27,29,31,50,57]. However, in other papers, red or green performed worse than the other colors [38,45]. Duart et al reported that the best-performing color is frequency-dependent, with no significant difference between the colors found for the frequencies above the medium-frequency band [31].…”
Section: Colormentioning
confidence: 96%
See 3 more Smart Citations
“…Green and colors with smaller wavelength such as red performed the best in terms of their SSVEP response, SNR and accuracy [14,27,29,31,50,57]. However, in other papers, red or green performed worse than the other colors [38,45]. Duart et al reported that the best-performing color is frequency-dependent, with no significant difference between the colors found for the frequencies above the medium-frequency band [31].…”
Section: Colormentioning
confidence: 96%
“…In several articles, the medium-band frequencies (with maxima at 13 Hz, 14 Hz, 15 Hz and 16 Hz) resulted in a higher SSVEP response, SNR and accuracy than the lower-band frequencies with the exception of 10 Hz, which is also a local maximum [14,25,27,31,36,37,45]. In contrast, some work also found higher responses at lower frequencies (e.g., 8.33 Hz) [40] or no significant difference [23].…”
Section: Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…However, the use of dry electrodes and the characteristics of AR perspective led to interference by various factors, resulting in overall low performance. Zhu et al ( 2023 ) examined the effects of shape, color, and frequency parameters on 3D SSVEP in a VR setting, but without specifically focusing on comparing the characteristics or performance differences between 3D stimulation and flat stimuli.…”
Section: Introductionmentioning
confidence: 99%